Chalkley Counting in Oral Tongue Squamous Cell Carcinoma:Does It have A Prognostic Value? - Paul Campbell; Reuben Bennet; Louisa Joyce Lim; Helen D Brasch; Reginald Marsh; Tinte Itinteang; Swee T Tan (Journal of Biotechnology and Biomedical Science, 2019)
Chalkley counting has been regarded as a relatively reliable method of quantifying tumor angiogenesis. In this study we investigated the reliability of Chalkley counting in quantifying tumor angiogenesis in oral tongue squamous cell carcinoma (OTSCC) using CD34; and tumor vasculogenesis using angiotensin converting enzyme, angiotensin II receptor 1 and angiotensin II receptor 2, in 32 OTSCC samples. Chalkley counting was performed by two independent observers. The averages of three ‘hot spot’ counts were compared with known prognostic factors. All four markers showed no correlation with any of the prognostic factors. When comparing the results from the two independent observers, the only marker shown to have a significant moderate correlation was CD34. The other three markers showed no significant correlation. The lack of statistical significance between the independent observers, and known prognostic factors with the four markers used, shows that Chalkley counting is not a reliable prognostic tool in OTSCC.
Keywords: Chalkley counting